Exploring oyster mushroom (Pleurotus ostreatus) substrate preparation by varying phase I composting time: changes in bacterial communities and physicochemical composition of biomass impacting mushroom yields - Vieira, F. R. [UNESP]; Pecchia, J. A.; Segato, F.; Polikarpov, I. (Wiley-Blackwell, 2019)
Aims To investigate characterization of the bacterial community composition and functionality and their impact on substrate biodegradation as well as mushroom yield. Methods and Results Bacterial diversity, composition and functionality were accessed by DNA-derived analysis for a sugarcane straw-based substrate composted for either 5, 10 or 15 days. In addition, carbon and nitrogen losses, carbohydrate conversion and mushroom yields were measured for the different treatments. Changes were observed in the bacterial community diversity and composition after the process started, but not during the composting process itself. Following phase I, Acinetobacter sequences were recovered in high numbers, and selected genes associated with nitrogen metabolism and lignocellulose deconstruction were mapped. Substrate physicochemical composition showed elevated carbon and nitrogen losses after 10 and 15 days of phase I with reductions in mushroom yield. Conclusions Acinetobacter species appear to play an important role in substrate degradation processes, and a 5-day phase I period showed a significant higher mushroom yield compared to composting for either 10 or 15 days. Significance and Impact of the Study: This study confers a better understanding of the bacterial community manipulation during the substrate preparation and their influence in substrate selectivity for the Pleurotus ostreatus cultivation.
Keywords: bacterial community; composting; metagenomics; mushroom yield; physicochemical changes; Pleurotus ostreatus